Effect of process variables in supercritical carbon dioxide extraction of tocotrienols from palm fatty acid distillate - Othman, Najwa (2021)
Palm fatty acid distillate (PFAD) is a by-product of palm oil refineries that have high valuable active compounds, specifically tocotrienols. It is commonly extracted using the conventional method, but, argued for its sustainability with the huge hazardous solvent residues, time consumption, and not suitable for thermo-labile compounds. Alternatively, the green sustainable technology, supercritical carbon dioxide (scCO2) extraction was employed in this work. Hence, the objectives of this study were to evaluate the effect of main process variables, namely pressure and temperature on the tocotrienols extraction and to determine optimal conditions for the recovery of tocotrienols using scCO2 extraction. In addition, investigation on the static mode (90 and 180 min) and solvent polarity modification by using single and pair mixtures co- solvent at optimum condition were also carried out to enhance the extraction of tocotrienols. The research began with the optimization process of tocotrienols extraction from pre-treated PFAD using scCO2 at a temperature range of 40-60 °C and pressure range of 20-40 MPa for a fixed CO2 mass flow rate of 32 ± 2 g/min and dynamic extraction time of 5 h through the Central Composite Design (CCD) with five replications of the central point. It was found that temperature had the most positive effect on the extraction of tocotrienols. The tocotrienols extraction was proportionally increased to a temperature from 40 up to 50 °C. Further increased temperature to 60 °C lowered the density of scCO2 hence, reduce the solubility of the interest compound to be extracted. Pressure is also a prominent factor in the extraction of tocotrienols. The predicted best condition (20 MPa and 53 °C) by response surface methodology (RSM) produced 16.45 mg/g of tocotrienols content. Static mode for 180 minutes does significantly improve the recovery of tocotrienols (23.62 ± 0.37 mg/g). The static mode was seen to promote the interest solute transfer through the enhancement of the permeability of cell walls by rupturing the sample. Besides, solvent polarity modification with aided of co-solvents significantly increased the tocotrienols content in the extracts. The content of tocotrienols was approximately double up (30.03 ± 0.03 mg/g) with the addition of 0.075 ml/g ethanol. Following that, the presence of 0.075 ml/g hydrogen bond donor (HBD)-hydrogen bond acceptor (HBA) pair mixtures co-solvent (isopropanol:acetone) resulted in the highest tocotrienols concentration (33.47 ± 0.29 mg/g). This indicated the chemical and physical interaction between the co-solvent and the interest solute molecule, thus, improved the solubility of tocotrienols in the scCO2 system. In summary, tocotrienols could be extracted from PFAD using scCO2 and further improved with slight modifications to the techniques. The solvent polarity modification of the scCO2 exhibited the best technique to improved the tocotrienols content, which may be related to the wide range of polarities. Herein, ethanol (0.075 ml/g) was chosen to improve the tocotrienols extraction since there were no significantly differences between single co-solvent of ethanol and pair mixtures co-solvent of isopropanol- acetone.